1997
DOI: 10.1097/00004647-199704000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Positron Emission Tomographic Studies in Transient Middle Cerebral Artery Occlusion in Cats: Residual Perfusion and Efficacy of Postischemic Reperfusion

Abstract: Summary:The wider clinical acceptance of thrombolytic therapy for ischemic stroke has focused more attention on experimental models of reversible focal ischemia. Such models enable the study of the effect of ischemia of various durations and of reperfusion on the development of infarc tions. We used high-resolution positron emission tomo graphy (PET) to assess cerebral blood flow (CBF), cere bral metatfolic rate of oxygen (CMR02), oxygen extraction fraction (OEF), and cerebral metabolic rate of glucose (CMRglc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 59 publications
7
84
1
Order By: Relevance
“…Classic PET studies in cats subjected to 30-120 min MCAo also showed that acute post-clip release hyperperfusion was associated with worse tissue outcome. 37 Another frequently observed post-MCAo phenomenon, also not observed here, is delayed hypoperfusion, i.e. a secondary drop in perfusion following early complete reperfusion.…”
Section: Immunofluorescencesupporting
confidence: 66%
“…Classic PET studies in cats subjected to 30-120 min MCAo also showed that acute post-clip release hyperperfusion was associated with worse tissue outcome. 37 Another frequently observed post-MCAo phenomenon, also not observed here, is delayed hypoperfusion, i.e. a secondary drop in perfusion following early complete reperfusion.…”
Section: Immunofluorescencesupporting
confidence: 66%
“…A "luxury perfusion syndrome" characterized by overabundant CBF relative to neuronal and glial metabolic demand is wellknown. 8,9 Much of our knowledge of postischemic reperfusion is derived from experimental models, 14 but the finding that postischemic hyperperfusion may include brain regions that become infarcted has also been demonstrated in small studies of human patients with stroke. 6 In 1 study of patients with stroke who underwent large-vessel recanalization with intra-arterial fibrinolysis, hyperperfusion was demonstrated in 5/12 by perfusion MR imaging several hours after recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of astrocytes to maintain these functions may, in fact, be a critical determinant of neuronal survival after ischemia (Aschner et al, 1999;Juurlink, 1997;Marrif and Juurlink, 1999;Stanimirovic etal, 1997). Furthermore, metabolic imaging studies have suggested that mitochondrial function in post-ischemic brain may be impaired for hours to days after the ischemic insult (Heiss et al, 1997;Hoehn-Berlage, 1995;Ogasawara et al, 2001;Takamatsu et al, 2000;Wardlaw et al, 1998). Loss of f m and eventual energy failure in astrocytes might lead to an inability to provide these critical support functions during ischemia, thus exacerbating ischemic injury to neurons.…”
Section: Discussionmentioning
confidence: 99%